Influence of TiO₂ Nanofluid Concentration on Friction Factor and Reynolds Number in Laminar–Turbulent Flow through 4 mm and 6 mm Acrylic Pipes - Hamzah Ali Nashirudin; Mohammad Samsul Bakhri; Deni Haryadi; Sri Poernomo Sari (Sultan Publisher, 2025)
This study examines the hydraulic and thermal performance of TiO₂–water nanofluids in small-diameter acrylic pipes, focusing on the influence of nanoparticle concentration and pipe geometry. Experiments were conducted using internal diameters of 4 mm and 6 mm, with TiO₂ volume concentrations of 0.3% and 0.5%. Nanofluids were prepared via a two-step method combining magnetic stirring and ultrasonic sonication to ensure uniform dispersion. Flow parameters, including Reynolds number, friction factor, and Nusselt number, were determined from measured pressure drop and flow rate data. Results show that increasing TiO₂ concentration elevates friction factor, with the effect more pronounced in smaller pipes due to intensified wall shear and higher surface-area-to-volume ratios. The 0.3% nanofluid consistently achieved higher Reynolds numbers and competitive heat transfer performance, while 0.5% concentration often reduced Nusselt number at equivalent flow conditions, likely due to viscosity-induced flow resistance and particle agglomeration. Deviations from classical laminar and turbulent correlations were observed, particularly in the transitional regime, indicating altered boundary layer behaviour. These findings highlight the need for optimised nanoparticle loading and diameter selection to balance heat transfer enhancement against hydraulic penalties in compact thermal management systems.